Moving target defense against network eavesdropping attack using POF - Duohe MA; Qiong LI; Dongdai LIN (Tongxin xuebao)
Eavesdropping attack hereby was the major attack for traditional network communication.As this kind of attacks was stealthy and untraceable,it was barely detectable for those feature detection or static configuration based passive defense approaches.Since existing encryption or dynamic address methods could only confuse part of fields of network protocols,they couldn’t form a comprehensive protection.Therefore a moving target defense method by utilizing the protocol customization ability of protocol-oblivious forwarding (POF) was proposed,through private protocol packet randomization strategy and randomly drop deception-packets on dynamic paths strategy.It could greatly increase the difficulty of implementing network eavesdropping attack and protect the privacy of the network communication process.Experiments and compare studies show its efficiency.